Teachers and Students Benefits for Bringing Oral Storytelling in Front of the Classroom - Tristan Rokhmawan; Daryono Daryono; Fuat Fuat; Inaad Mutlib Sayer; Xenia Konstantinopoulou; Nuril Mas’udah; Durotun Nafisah (CV. Creative Tugu Pena, 2022)
Elementary school or Madrasah Ibtidaiyah teachers' competence in oral storytelling was needed as a form of role model for students to be able to develop their skills. It was caused to be able to develop speaking, students need exposure to listening material. Teachers need to create an atmosphere that allows students to practice using spoken language. Based on the results, in the context of learning at the basic education level for children, storytelling is able to increase the potential of their language skills by listening, then children are expected to be able to reflect back on the story in oral form. This article aimed to give an assistance of 5 teachers and 25 students of oral storytelling to get benefit of language skill. The researchers used Service Learning (SL) approach (Felten, & Clayton, 2011). It as a medium for integrating voluntary community service with active reflection which is expected to enrich and strengthen the material about bringing oral storytelling in developing students and teachers. Analyzing data used modeling, asignment, perform (Topi & Ramesh, 2002). Finally, the final results of all of our activities in the context of community service are: 1) There is a change in the behavior of teachers and students to develop activities based on oral storytelling skills, 2) The development of an oral storytelling culture, 3) An increase in oral storytelling skills, and 4 ) The emergence of awareness to find many oral stories in traditional societies that have not been widely written or spoken in a formal context. Keywords: Oral Storytelling, Assistance Oral Storytelling, Benefits Oral Storytelling